Exploration of Organic Mushroom Forms in The Design of Aesthetic and Functional Nakas - Sari, Dina Mariana; Sasmita, Rika Febri; Rohiman, Rohiman; Yusuf, Andi Wahyu Zulkifli; Wijaya, Meylinda Putri (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Modern furniture design is increasingly focusing on aesthetics, functionality, and sustainability. One of the innovative approaches to furniture design is biomimicry, which is adapting the natural shape of the mold into the design of the product. This study explores the visual characteristics of mushrooms to be applied in the design of aesthetic and functional nightshades. The research method used is qualitative. Literature studies, observation of fungal shapes, sketch experiments, 3D models, and prototyping were carried out to understand the structure and texture of fungus. Some of the types of fungi observed are Agaricus bisporus, Pleurotus ostreatus, and Ganoderma lucidum which have potential in furniture design. The data analysis technique used is ergonomics analysis. The ergonomic analysis of the design of the mushroom organic shaped nightstand emphasizes the fit between aesthetics and function. The results of the study show that the organic form of the mushroom can be effectively adapted in the design of the nightshade, optimizing aesthetics and ergonomics. The design sketches were developed based on biomimicry principles, then tested through digital models and prototypes made of mycelium and sustainable wood. Functionality tests prove that this design not only enriches the visual value of the furniture but also improves the space efficiency as well as the durability of the product. In conclusion, the exploration of the organic forms of mushrooms in nightstand design offers an innovative solution for the furniture industry by combining natural aesthetics, ergonomics, and sustainability. With a biomimicry approach, this design can be a reference for the development of furniture products based on natural inspiration that are more innovative and environmentally friendly.